Ethnobotanic resources of tropical montane forests : Indigenous uses of plants in the Cameroon highland ecoregion - Ndenecho, Emmanuel Neba (Langaa Research & Pub. CIG, 2011)
Mountain forests provide important ecological services, and essential products. This book focuses on the importance of mountain forests in Cameroon for the local people who depend most directly on them, and have often developed a wealth of Indigenous knowledge on plants and sophisticated institutions for managing limited plant and animal resources. Such knowledge and institutions have often been threatened, or even destroyed, by centralization and globalization; yet there is increasing recognition that community-based institutions are the best adapted to ensuring that mountain forests continue.